1953
DOI: 10.1161/01.res.1.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Vasomotor Innervation of the Dog's Hind Footpad

Abstract: Vascular responses in the large central pad of the dog's foot were recorded during stimulation of the lumbosacral sympathetic trunk and correlated with the site of stimulation and the subsequent histologic analysis of the excised trunk. The resulting description of the preganglionic inflow and postganglionic outflow from the trunk demonstrated marked variations in the anatomic patterns of the vasomotor innervation of the footpad in various animals. Complete preganglionic denervation of this vascular bed requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1954
1954
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The data presented here are in accord with an earlier study by Randall and associates (4) in that vasoconstrictor responses were obtained from stimulation of the lumbar sympathetic chain as far caudal as the sacral level. A difference, however, is that in the present study the preganghonic inflow to the lumbar sympathetic trunk of vasoconstrictor fibers terminated at L-4, L-5, whereas these authors indicated inflows as far caudal as L-7.…”
Section: Donald Fergusonsupporting
confidence: 90%
“…The data presented here are in accord with an earlier study by Randall and associates (4) in that vasoconstrictor responses were obtained from stimulation of the lumbar sympathetic chain as far caudal as the sacral level. A difference, however, is that in the present study the preganghonic inflow to the lumbar sympathetic trunk of vasoconstrictor fibers terminated at L-4, L-5, whereas these authors indicated inflows as far caudal as L-7.…”
Section: Donald Fergusonsupporting
confidence: 90%
“…The former authors suggested that the decrease in trunk skin temperature could be explained by vasoconstriction of trunk skin vessels above, and potentially also within, the analgesic areas [16]. This is an attractive hypothesis because the sympathetic system seems to be poorly organized, with sympathetic efferents overlapping several dermatomes [26][27][28], and blood flow to the upper extremity has been reported to decrease during both extradural and spinal anaesthesia with a T4 sensory level [4,6,8] possibly as a result of baroreflex activation by the accompanying decrease in arterial pressure.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Preganglionic sympathetic fibres ascend and descend in the paravertebral sympathetic chain before synapsing with postganglionic neurones both above and below their segmental points of origin [2,20,21]. Those supplying the hind limbs could have emerged from the spinal cord at a much higher level than the sensory nerves of the lower extremity enter it, resulting in segmental analgesia restricted to only the upper thorax, but also in widespread sympathetic block involving the hind limbs with high thoracic extradural injection.…”
Section: Discussionmentioning
confidence: 99%